INTELLIGENT RADIOACTIVE WASTE INACTIVATION AUTOMATION SYSTEM - Tsagaris, Apostolos; Taousani , Margarita; Mylonas, Georgios (Journal of Applied Engineering Science, 2024)
The paper deals with the implementation of an intelligent automation system that ensures the smooth operation of a radioactive waste inactivation system as well as the SCADA system responsible for monitoring the entire automation system. It includes the inspection of five radioactive waste management tanks and a central radioactive waste collection pit of a Nuclear Medicine laboratory. The purpose was to create an intelligent automation system with PLC with the possibility of the future expansion of the reservoirs after an increase in hospitalized patients. Object-oriented programming was used with modern control code development techniques, but also visualization of all necessary information. The states tested for system operation are Collection, Treatment, and Wastewater Waiting. Each of the 5 collection tanks has a level sensor, safety float, sewage agitation system, sewage inlet and outlet valves, wash valve, and sampling valve. The system has a central valve that directs wastewater from patient rooms receiving radioactive iodine treatment either to the quench tank system via a central sump or to the central sewer system. Active sewage is collected in the central well and pumped to the collection tank. The central well has a level sensor to activate the pumps and a safety float.